Lung Cancer Modern Multidisciplinary Management - Park, Henry S. (IntechOpen, 2021)
Lung cancer continues to be the leading cause of cancer mortality worldwide among both men and women. Recent advances in prevention, screening and management in the past decade have led to significant improvements in survival and quality of life. Local treatments like minimally invasive surgery, radiotherapy, and image-guided ablation have contributed to improving the effectiveness and tolerability of potentially curative treatments in early-stage, locally advanced, and oligometastatic/oligoprogressive disease. Chemotherapy, targeted therapy, immunotherapy, and palliative local therapy options have expanded rapidly, with new regimens showing improved outcomes even for those with widely metastatic disease. This book comprehensively reviews the evidence that has driven personalized medicine, based on a variety of multidisciplinary perspectives by international lung cancer experts.